2008
DOI: 10.1210/jc.2008-0821
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms inCLEC16AandCIITAat 16p13 Are Associated with Primary Adrenal Insufficiency

Abstract: Two alleles at 16p13 are independently associated with the risk of Addison's disease in the Norwegian population, suggesting this chromosomal region to harbor common autoimmunity gene(s), CLEC16A and CIITA being possible independent candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 32 publications
(33 reference statements)
3
87
1
3
Order By: Relevance
“…15 Mutations in another gene of this family known as caspase recruitment domain 15 (CARD 15) or NOD2 is associated with Crohn's disease, 16 early-onset sarcoidosis and Blau syndrome characterized by granulomatous synovitis, non-granulomatous uveitis and cranial neuropathies. 14,17 Mutations in NALP3 coding for cryopyrin are causative for the auto-inflammatory diseases, such as familial cold autoinflammatory syndrome, the MuckleWells syndrome and neonatal-onset multisystem inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…15 Mutations in another gene of this family known as caspase recruitment domain 15 (CARD 15) or NOD2 is associated with Crohn's disease, 16 early-onset sarcoidosis and Blau syndrome characterized by granulomatous synovitis, non-granulomatous uveitis and cranial neuropathies. 14,17 Mutations in NALP3 coding for cryopyrin are causative for the auto-inflammatory diseases, such as familial cold autoinflammatory syndrome, the MuckleWells syndrome and neonatal-onset multisystem inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies have identified an association of the CLEC16A (C-type lectin domain family 16, member A) locus with type 1 diabetes (T1D) [1,2] and a number of other autoimmune (AI) diseases, such as multiple sclerosis (MS), Addison's disease (AD) and autoimmune thyroid disease [3][4][5][6]. This association spans a 233 Kb linkage disequilibrium (LD) block and has been replicated in other T1D cohorts [7][8][9][10], as well as those of other AI diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…In our screening panel, we genotyped one SNP downstream of SOCS1, rs243329 (P ¼ 0.03), which has been found associated with T1D, and one SNP in CIITA, rs8048002 (P ¼ 0.71), which has shown association with Addison's disease. 7,9 Both SNPs should based on low LD (D 0 o0.35, r 2 o0.1), be independent of the CLEC16A-associated SNPs found in MS (see Supplementary Figure 1). Still, evidence of a role for SOCS1 and CIITA in MS is emerging.…”
Section: Discussionmentioning
confidence: 93%
“…As the TaqMan assay did not work for one of the top hit SNP (rs6498168), we replaced this SNP with one in complete LD (r 2 ¼ 1; rs8060411), which was then genotyped in both the screening cohort and the replication cohorts. A total of 1029 Norwegian blood donors were previously genotyped for rs12708716 by Skinningsrud et al 7,8 For the 1958 birth controls, SNPs rs9934231, rs12708716, rs6498169 and rs12923849, had already been genotyped by the Wellcome Trust Case-Control Consortium and, hence, their genotypes were obtained through the Wellcome Trust Case-Control Consortium website (www.wtccc.org.uk). Further, SNP rs12708716 has previously been genotyped in the complete UK cohort .and does not represent new data.…”
Section: Snp Panel Design and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation